Модели основных базисов единой электроэнергетической системы Украины - Левыкин, В. М.; Кудрявцева, М. С. (My University, 2009)
Розроблено структурно-функціональну схему електричної частини енергосистеми, отримані моделі основних базисів Єдиної електроенергетичної системи України з урахуванням її ієрархічної та розподіленої структури. The structural and functional scheme of electrical part of power supply system is developed in this work. The models of fundamental basisys of Ukraines’ Uniform power supply system taking into account hierarchical and distributed structure are obtained.
Keywords: единая электроэнергетическая система; системный оператор; подстанция; регулярная схема системной модели